Heat Assisted Magnetization Reversal on Perpendicular Magnetized Nano-Dot - Nur Aji Wibowo; Cari Cari; Budi Purnama (IPTEK The Journal for Technology and Science, 2011)
Heat assisted magnetization reversal on perpendicular magnetized nano-dots has been studied by solved Landau Lifshift-Gilbert equation for magnetic recording application. The heat assisted magnetization reversal scheme has been proven to be effectively reduces threshold field down to 90 %. Otherwise, this field doesn’t depend on heating time. To understand a read-write information process, cooling time dependence of threshold field has been evaluated. As a result, the threshold field depends on the cooling time and become constant after 300 ps. This result corresponds to data transfer of Hard Disc Drive about 30 Gb/s.